PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA PEMBELAJARAN TEKS EKSPOSISI - Riyan, Muhamad (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
Learning media is important for the continuity of learning activities so that these activities jave variations that make students not bored. One of them is with android-based learing media. The android-based learning media is form of alignment in the field of education with advances in the field of technologu. This study aims to produce android-based learning media as a form of learning variation in exposition texts. In addition, this study also aims to see student responses to android-based learning applications. This research method uses a qualitative descriptive method with interview techniques. The object of this research is an application that is organized according to the subject matter and also a review of this android-based learning application. The results of this study indicate that this android-based learning media application has good feasibility to be used as a variation of new learning media in Indonesian lessons.Keywords: Media, learning, android, text, exposition